PERANCANGAN DAN ANALISIS PERFORMA POMPA HIDRAM UNTUK MEMENUHI KEBUTUHAN AIR BERSIH DI DUSUN BELANG TLOGOLELE SELO BOYOLALI - Deni Andriyansyah; Yuyun Estriyanto; Danar Susilo Wijayanto (Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2014)
This research aimed to: (1) determine the daily water needs of Belang population, (2) designinghydram pump installation based on water needs and geographical conditions of Belang village, (3) study theperformance and efficiency of the hydram pump, (4) study the role of the hydram pump to fulfill the dailywater needs of Belang population. This study was based on Research and Development (R & D). Itdeveloped hydram pump installation to fit the topography of Belang village so it can work optimally. Thepump was tested by varying waste valve length at 20 mm, 25 mm, 30 mm and 35 mm; and waste valve ballastat 0 grams, 250 grams, 500 grams and 750 grams. Data collection was performed three times for eachvariation. Hidram pump performance was determined by the efficiency and the volumetric discharge of waterproduced during the pump operation. Hydram pump was designed based on standard of the daily waterneeds which reachs 13650 liters/ day for 195 Belang’s people. In this study, hydram pump has someparameters. They are 4,5 meters of supply height, 80 meters of delivery height, 4 inches of pump bodydiameter and 1 inch of delivery pipe. Based on the tests that have been conducted, the highest efficiency ofthe hydram pump shown at 30 mm of waste valve length and 250 grams of waste valve ballast (η = 0.486652,q = 6.746969 L / min). The maximum volumetric discharge was presented at 35 mm of waste valve lengthand 750 grams of waste valve ballast (q =7.522211 L / min, η = 0.380989). Hydram pump performancecould fulfill the water needeed in Belang Village until medium term maintenance level. They could use thewater for drinking, cooking, bathing, washing, until cleaning home by 9750 liters/ day.